Effects of turbulization on the disc pump performance (2019)
Disc pumps are used for difficult pumping applications, such as, pumping of high suspension solids and abrasives, viscous fluids, air entrained and shear sensitive fluids. The pumping mechanism, based on the boundary layer effect and the viscous drag minimizes the contact between the pump and the fluid reducing the wear level; but the pumping mechanism itself makes its efficiency low in comparison with other pumps for similar applications. This research aims to increase the performance of this pump developing a new experimental study based on the turbulization of flow by the placement of turbulizers in the interdisc channel output. The variables involved are the angular velocity (x) and the cross section shape of the turbulizers. Eight impellers were constructed and evaluated using as cross section shape of turbulizers: the triangular, circular, and square. The experimental results show that the creation of circulatory currents, according to the Kutta-Johkovsky theorem, contributes to the increase the efficiency and the head of the disc pump and the square cross section shape of the turbulizers offers the best results.